2017
DOI: 10.1111/fwb.12965
|View full text |Cite
|
Sign up to set email alerts
|

Responses of benthic algal communities and their traits to experimental changes in fine sediments, nutrients and flow

Abstract: Summary Lowland stream ecosystems are subjected to multiple anthropogenic stressors, usually nutrient enrichment in combination with sedimentation of fine particles and low flow periods in summer. Here, we investigated the temporal development of the benthic algae community in response to these three stressors and linkages to the trait characteristics of the community to explore the mechanisms responsible for stress‐induced community changes. We investigated the response of benthic algae species composition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 51 publications
3
18
0
Order By: Relevance
“…A number of studies involving benthic diatom assemblages or algal communities have related community changes to abiotic factors other than water quality. The relationship between diatoms and river discharge has been demonstrated (Molloy, 1992;Passy, 2001;Neif et al, 2017) and a number of studies on river regulation have related diatom assemblage changes to flow alteration (Peterson, 1986;Growns, 1999;Cibils Martina, Principe & Gari, 2013). Taxa within the low-profile guild are likely to thrive in frequently disturbed habitats, whereas high-profile taxa are typically prevalent in conditions with little physical disturbance (Passy, 2007;Stenger-Kovács et al, 2013).…”
Section: Possible Drivers Of Diatom Assemblage Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies involving benthic diatom assemblages or algal communities have related community changes to abiotic factors other than water quality. The relationship between diatoms and river discharge has been demonstrated (Molloy, 1992;Passy, 2001;Neif et al, 2017) and a number of studies on river regulation have related diatom assemblage changes to flow alteration (Peterson, 1986;Growns, 1999;Cibils Martina, Principe & Gari, 2013). Taxa within the low-profile guild are likely to thrive in frequently disturbed habitats, whereas high-profile taxa are typically prevalent in conditions with little physical disturbance (Passy, 2007;Stenger-Kovács et al, 2013).…”
Section: Possible Drivers Of Diatom Assemblage Changesmentioning
confidence: 99%
“…The influence of temperature on diatom assemblages has also been reported (Bergey, Desianti & Cooper, 2017), and thermal alteration by impoundment has been shown to induce changes to assemblage composition within a short time-period (Blinn, Truitt & Pickart, 1989). In addition, the relationship between diatom motility and fine sediment has been demonstrated, although some studies indicated that there may be confounding effects of other environmental pressures (Jones et al, 2014;Neif et al, 2017;Jones et al, 2017).…”
Section: Possible Drivers Of Diatom Assemblage Changesmentioning
confidence: 99%
“…This suggests that algal biomass accumulation was extremely limited once TSS levels exceeded the threshold. Algae growing in systems that are beyond the TSS threshold are likely highly tolerant to sedimentation and may be more resistant to sediment scour (Francoeur & Biggs, 2006;Neif et al, 2017) or have the ability to photo-acclimate to low-light conditions (Hill, Ryon, & Schilling, 1995;Rhee & Gotham, 1981). Van Nieuwenhuyse and LaPerriere (1986) saw a 50% decrease in primary production in streams in the interior highlands of Alaska at levels of 200 mg/L TSS.…”
mentioning
confidence: 99%
“…A number of studies involving benthic diatom assemblages or algal communities have related community changes to abiotic factors other than water quality. The relationship between diatoms and river discharge has been demonstrated (Molloy, 1992;Passy, 2001;Neif et al, 2017) and a number of studies on river regulation have related diatom assemblage changes to flow alteration (Peterson, 1986;Growns, 1999;Cibils Martina et al, 2013). Taxa within the low-profile guild are likely to thrive in frequently disturbed habitats, whereas high-profile taxa are typically prevalent in conditions with little physical disturbance (Passy, 2007;Stenger-Kovács et al, 2013).…”
Section: Possible Drivers Of Diatom Assemblage Changesmentioning
confidence: 99%
“…The influence of temperature on diatom assemblages has also been reported (Bergey et al, 2017), and thermal alteration by impoundment has been shown to induce changes to assemblage composition within a short time-period (Blinn et al, 1989). In addition, the relationship between diatom motility and fine sediment has been demonstrated, although some studies indicated that there may be confounding effects of other environmental pressures (Jones et al, 2014;Neif et al, 2017;Jones et al, 2017).…”
Section: Possible Drivers Of Diatom Assemblage Changesmentioning
confidence: 99%